The Role of Digital Marketing, Service Quality, Product Quality on Purchasing Power through the Satisfaction of Probolinggo MSME Followers during the Covid-19 Pandemic - Yuyun Sumarlinah; Sukesi Sukesi; Sugiyanto Sugiyanto (International Journal of Applied Business and International Management, 2022)
This study aims to analyze the role of digital marketing, service quality, and product quality on purchasing power through consumer satisfaction of the MSME followers processing and marketing marine and fishery products in Probolinggo City during the Covid-19 pandemic. This study used 225 respondents for the object of the study. The results showed that the role of digital marketing, service quality, and product quality affect consumer satisfaction. Furthermore, the consumer satisfaction affects purchasing power. In addition, the role of digital marketing, service quality, and product quality affect consumer purchasing power. However, the role of digital marketing, service quality, and product quality does not affect consumer purchasing power through consumer satisfaction as an intervening variable. It implies that the MSME actors can adapt to changes in the business environment, allowing them to survive and be responsive to any changes.